2013
DOI: 10.1016/j.cca.2012.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metal distribution in scalp hair of Pakistani and Irish referents and diabetes mellitus patients

Abstract: Background: The essential metals, chromium (Cr), magnesium (Mg), manganese (Mn) and zinc (Zn), are necessary for many metabolic processes and their homeostasis is crucial for life. The toxic metals, cadmium (Cd) and lead (Pb), have no beneficial role in human metabolism. The aim of this study was to investigate the levels of Cd, Cr, Mg, Mn, Pb, and Zn in scalp hair samples of type 2 diabetes mellitus patients of both genders, ages ranging from 30 to 50 y, and belong to urban areas of Ireland and Pakistan. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 73 publications
5
14
0
3
Order By: Relevance
“…Similar results have been reported by other studies (11,16,20). Epidemiological studies showed a high prevalence of hypomagnesemia and lower intracellular Mg concentration in patients with DM (21).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar results have been reported by other studies (11,16,20). Epidemiological studies showed a high prevalence of hypomagnesemia and lower intracellular Mg concentration in patients with DM (21).…”
Section: Discussionsupporting
confidence: 82%
“…This result was consistent with the findings of different authors (11,14). Hyperglycemia and high levels of insulin increase Cr excretion; thus, low hair levels of Cr may be seen in patients with DM (14).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…High concentrations of cadmium (Cd) and Pb were found in scalp hair samples of diabetic patients in Pakistan and Ireland (Afridi et al 2013). The involvement of metals has also been implicated in the development of Parkinson's disease (Bocca et al 2006).…”
Section: Introductionmentioning
confidence: 99%